An Efficient Method for the Protection of Aromatic Amines with Benzostabase and Its Utility in Anionic Aromatic Transformations - Lu, Erhu; Yadav, Arun; Weaver, Donald F.; Reed, Mark A. (Synlett, 2013)
Herein we describe an efficient and generally applicable method of protecting a diverse series of aromatic amines with the ‘benzostabase’ group. We also demonstrate its efficient use in aromatic anionic chemistry including its utility in the anionic ortho Snieckus–Fries rearrangement.
Keywords: benzostabase; stabase; in situ protection; directed ortho Metalation; anionic ortho Snieckus–Fries rearrangement